Striatal morphology and neurocognitive dysfunction in Huntington disease: The IMAGE-HD study. (30th September 2019) - Wilkes, Fiona A.; Abaryan, Zvart; Ching, Chris R.K.; Gutman, Boris A.; Madsen, Sarah K.; Walterfang, Mark; Velakoulis, Dennis; Stout, Julie C.; Chua, Phyllis; Egan, Gary F.; Thompson, Paul M.; Looi, Jeffrey C.L.; et al.
Highlights: Neostriatal shape differences were detected between controls, pre-HD, and symp-HD. These shape changes were associated with measures of disease burden. Neostriatal shape changes also correlated with motor and neurocognitive measures. Abstract: We aimed to investigate the relationship between striatal morphology in Huntington disease (HD) and measures of motor and cognitive dysfunction. MRI scans, from the IMAGE-HD study, were obtained from 36 individuals with pre-symptomatic HD (pre-HD), 37 with early symptomatic HD (symp-HD), and 36 healthy matched controls. The neostriatum was manually segmented and a surface-based parametric mapping protocol derived two pointwise shape measures: thickness and surface dilation ratio. Significant shape differences were detected between all groups. Negative associations were detected between lower thickness and surface area shape measure and CAG repeats, disease burden score, and UHDRS total motor score. In symp-HD, UPSIT scores were correlated with higher thickness in left caudate tail and surface dilation ratio in left posterior putamen; Stroop scores were positively correlated with the thickness of left putamen head and body. Self-paced tapping (slow) was correlated with higher thickness and surface dilation ratio in the right caudate in symp-HD and with bilateral putamen in pre-HD. Self-paced tapping (fast) was correlated with higher surface dilation ratio in the right anterior putamen in symp-HD. Shape changes correlated with functional measures subserved by corticostriatal circuits, suggesting that the neostriatum is a potentially useful structural basis for characterisation of endophenotypes of HD.